Analisa dan Perancangan Sistem Aplikasi Rental Mobil Berbasis Perangkat Android - Ahmad Fadli; Arisky Rahmatulloh; Irwan Ahussalim; Ridho Hafizh Maulana; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Departing from several problems experienced by many loan or car rental service providers in the Jabodetabek area, including the problem of timeliness of returning car loans by customers and monitoring the area according to the information at the beginning of the loan. Based on our observations, we took the initiative to make a breakthrough that could later be utilized by car loan service providers in the Greater Jakarta area which aims to provide easy assistance in monitoring customers who use the car loan service so that it can be returned to the car/business owner as appropriate time. The results achieved from the design and use of this application are the added value of convenience for rental owners who can easily monitor their cars being rented by customers and also convenience for customers who can access car rental services only through the gadget they have.